Cameroonian Pre-service Science Teachers' Conceptions of the Nature of Science and its Determinants. - Nchia, Lawrence Ntam; Bouni, Ayina; Jeremie, Awomo Ateba; Halidou, Hamadou (Journal of Education and Practice, 2024)
Purpose: The inadequacy knowledge about the nature of science (NOS) motivated the researchers to investigate Pre-service teachers' conception and their determinant in view of proposing strategy to overcome them and effectively train pre-service science teachers to efficiently implement the competency based approach to teaching, learning and evaluation of sciences. Methodology: A cross sectional descriptive survey was carried out on a purposeful and convenient sample of 118 Pre-service teachers of Higher Teacher Training College Yaound using MOSQ questionnaire. Descriptive and inferential statistical analysis of data was done using SPSS V23. Findings: More than half of respondents held an informed correct view only on their conception of scientific enterprise and non-coherent uniformed views about scientific knowledge, scientific method and scientists' work. The major inconsistency and misconception was about hierarchical relationship between hypothesis, theories and laws and cumulative nature of scientific knowledge. These misconceptions was determined by the department the students belong to and not by their age, sex, religion or level of education. Physics pre-service teachers were more informed about NOS compared to Chemistry and Biology teachers, with the least informed being pre-service teachers of History & Geography departments. Unique contribution to theory, practice and policy: These results fills the knowledge gap about teachers' conception of NOS in the Cameroonian context. It has practical implication in the designing of didactic strategies to overcome these misconceptions and bring about conceptual change in pre-service teachers. Including NOS implicitly or explicitly in the science curriculum will enhance scientific literacy in teachers and eventually students.